An algorithm for computing zeros of generalized phi-strongly monotone and bounded maps in classical Banach spaces. (2nd April 2016) - Chidume, C.E.; Chidume, C.O.; Bello, A.U.
Abstract : Let, , and be a generalized -strongly monotone and bounded map with . An iterative process is constructed and proved to converge strongly to the unique solution of the equation . In the special case in which is the subdifferential of a proper convex function, a solution of corresponds to a minimizer of . Furthermore, our technique of proof is of independent interest.